Consumer Surplus Changing in the Transition from State Natural Monopoly to the Competitive Market in the Electricity Sector in the Developing Countries: Azerbaijan Case - Gulaliyev, Mayis Gulali; Yuzbashiyeva, Gulshen Zahidqizi; Mamedova, Gulnara Vaqifqizi; Abasova, Samira Tahmazqizi; Salahov, Fariz Rafiq; Askerov, Ramil Ramiz (International Journal of Energy Economics and Policy, 2020)
The objectives of the study are to analyze changes in consumer surplus and protect the social interest of poor households in the transition from a state monopoly over the electricity sector to the market. For this purpose, the volume of household electricity consumption by various incomes was calculated, the electricity demand function of households and the marginal cost of generating electricity were constructed. A methodology is given for calculating the electricity demand function for households and prices in an equilibrium market. The consumer surplus and its change are calculated. As well as there are given some recommendations to reduce the social burden for certain household groups while raising prices in the transition from a monopoly to the market, and the amount for the state subsidy for poor households. Keywords: consumer surplus, producer surplus, electric power sector, pricing, marginal cost, average costs JEL Classifications: D42, L51 DOI: https://doi.org/10.32479/ijeep.8909